2011
DOI: 10.1167/11.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Color responsiveness argues against a dorsal component of human V4

Abstract: The retinotopic organization, position, and functional responsiveness of some early visual cortical areas in human and non-human primates are consistent with their being homologous structures. The organization of other areas remains controversial. A critical debate concerns the potential human homologue of macaque area V4, an area very responsive to colored images: specifically, whether human V4 is divided between ventral and dorsal components, as in the macaque, or whether human V4 is confined to one ventral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 85 publications
4
49
0
Order By: Relevance
“…Given the established role of the V4 complex in color-related processing, could stimulating the ATL interfere with neural processing of V4, thereby abolishing the color effect? If this were the case, we would expect that stimulation of the OP ( V1 of the visual cortex) would similarly abolish the color effect, as it is anatomically closer to V4 than is the ATL and hosts multiple color-sensitive subregions that send signals to V4 for further processing (Goddard, Mannion, McDonald, Solomon, & Clifford, 2011;Shapley & Hawken, 2011). Contrary to this possibility, however, our results showed that the color congruency effect remained robust after the stimulation of the OP, making this an unlikely explanation.…”
Section: Discussionmentioning
confidence: 53%
“…Given the established role of the V4 complex in color-related processing, could stimulating the ATL interfere with neural processing of V4, thereby abolishing the color effect? If this were the case, we would expect that stimulation of the OP ( V1 of the visual cortex) would similarly abolish the color effect, as it is anatomically closer to V4 than is the ATL and hosts multiple color-sensitive subregions that send signals to V4 for further processing (Goddard, Mannion, McDonald, Solomon, & Clifford, 2011;Shapley & Hawken, 2011). Contrary to this possibility, however, our results showed that the color congruency effect remained robust after the stimulation of the OP, making this an unlikely explanation.…”
Section: Discussionmentioning
confidence: 53%
“…Standard criteria were used to delineate the borders of the low-level visual areas V1, V2, and V3 (Dougherty et al, 2003; Schira, Tyler, Breakspear, & Spehar, 2009). The ventral mid-level human V4 region (hV4) was defined as a full contralateral hemifield representation extending posterior to the ventral V3 border (Arcaro, McMains, Singer, & Kastner, 2009; Goddard, Mannion, McDonald, Solomon, & Clifford, 2011; Wade, Brewer, Rieger, & Wandell, 2002). We delineated three regions of dorsal mid-level cortex; LO1, LO2, and V3A/B.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas some have argued that human V4 consists of a dorsal and ventral part (V4v and V4d) (Hansen et al, 2007), differences in retinotopy and functional properties suggest that these two human cortical regions are distinct. Unlike V4v, putative human V4d does not respond more strongly to color than to grayscale stimuli (Tootell and Hadjikhani, 2001;Wade et al, , 2008Winawer et al, 2010;Goddard et al, 2011). Macaque V4v (adjacent to V3v) and V4d (adjacent to V3d) represent complementary parts of the contralateral hemifield.…”
Section: Macaque Versus Human Color Visionmentioning
confidence: 99%